Be a man or become a nurse: Comparing gender discrimination by employers across a wide variety of professions - Dorothea Kübler; Julia Schmid; Robert Stüber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
We investigate gender discrimination and its variation between firms, occupations, and industries with a factorial survey design (vignette study) for a large sample of German firms. Short CVs of fictitious applicants are presented to human resource managers who indicate the likelihood of the applicants being invited to the next step of the hiring process. We observe that women are evaluated worse than men on average, controlling for all other attributes of the CV, i.e., school grades, age, information about activities since leaving school, parents' occupations etc. Discrimination against women varies across industries and occupations, and is strongest for occupations with lower educational requirements and of lower occupational status. Women receive worse evaluations when applying for male-dominated occupations. Overall, the share of women in an occupation explains more of the difference in evaluations than any other occupation- or firm-related variable.
Keywords: C99; J71; 330; gender discrimination; hiring decisions; vignette study